effect تأثير بعض أنواع البكتريا المحفزة لنمو النبات (PGPR) في الحد من الإصابة بفطر Fusarium solani على نبات الكوسا: المقدمة (Journal of Hama University, 2025)
Abstract    The research aimed to study the effect of three types of bacteria that stimulate plant growth (Bacillus circulans, Bacillus megaterium, and Azotobacter chroococcum) in reducing the effect of the fungus Fusarium solani and its symptoms on zucchini plants grown in bags, and to measure some vegetative growth indicators related to the number of leaves on the plant and the fresh weight of the two groups. Vegetative and root.    The results showed a reduction in the symptoms of infection with the pathogenic fungus F. solani, and the F+Bc treatment was the best, followed by the F+Bm treatment, then the F+Az treatment. It also showed an increase in the growth of zucchini plants and a reduction in the effect of the pathogenic fungus on the number of leaves and the fresh weight of the shoot and root systems compared to the healthy control and the fungus-infected control not treated with bacteria. The bacterial species B. circulans was superior in reducing the effect of the fungus F. solani on zucchini plants, followed by the bacterial species B. megaterium and then the bacterial species A. chroococcum in all the indicators studied. Therefore, it is possible to use bacterial inoculation with the bacterial species B. circulans, B. megaterium, and A. chroococcum by adding them to plant seedlings to improve their growth, productivity, and resistance to plant diseases.Keywords: PGPR, Fusarium solani, pathogenic, inoculum, infection, zucchini plant*. Associated Professor, Department of soil and water sciences, Faculty of Agriculture Engineering, Tishreen University, Lattakia, Syria. Yaser.hammad@tishreen.edu.sy** Assistant, second faculty of agriculture in suwayda, Damascus university. ramez2.alshami@damascusuniversity.edu.sy
Keywords: PGPR, Fusarium solani, pathogenic, inoculum, infection, zucchini plant